Is Loop Ileostomy in Patients with Cecal Bascule a Viable Option? - Tushar Shetty; Tommy Ivanics; Hassan Nasser; Amalia Stefanou (Case Reports in Surgery)
Background. Cecal bascule, initially described in 1899 by Treves, is the rarest form of cecal volvulus and represents a phenomenon when a redundant and distended cecum folds anteriorly over the ascending colon causing an intestinal obstruction. Patients with cerebral palsy are at increased risk for this condition. Case Presentation. We present a 28-year-old male with cerebral palsy, functionally dependent in all activities of daily living, who had undergone a loop ileostomy for cecal bascule. He then presented to our emergency department with a large loop ileostomy prolapse, which was the result of an inverted prolapsed cecum through the efferent ileostomy limb. He underwent a right hemicolectomy with end ileostomy and transverse mucous fistula creation through the previous ostomy site. He progressed well appropriately postoperatively and was discharged home. Conclusions. While cecal bascule is a rare form of bowel obstruction, patients with cerebral palsy are at an increased risk for this condition. The treatment options are numerous and are primarily surgical. Diverting loop ileostomy alone is not a recommended treatment. A high index of suspicion is warranted in all cases of large bowel obstruction to minimize risk of recurrence, morbidity, and mortality for patients afflicted by this condition.